2010
DOI: 10.1261/rna.2008110
|View full text |Cite
|
Sign up to set email alerts
|

Induced fit or conformational selection for RNA/U1A folding

Abstract: The hairpin II of U1 snRNA can bind U1A protein with high affinity and specificity. NMR spectra suggest that the loop region of apo-RNA is largely unstructured and undergoes a transition from unstructured to well-folded upon U1Abinding. However, the mechanism that RNA folding coupled protein binding is poorly understood. To get an insight into the mechanism, we have performed explicit-solvent molecular dynamics (MD) to study the folding kinetics of bound RNA and apo-RNA. Roomtemperature MD simulations suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 67 publications
4
54
0
Order By: Relevance
“…More recently, Qin et al have reported kinetic and freeenergy landscape analyses of a set of MD simulations, which suggested that the SL2 RNA associates with U1A by a process that involves an initial association followed by folding of the RNA into the bound conformation. 90 The three-step dissociation model proposed by Tang and Nilsson was supported by studies of association and dissociation by SPR and computational modeling studies. 41,44,81 The results of these investigations suggested that the U1A complex is formed by at least two steps that were termed the "lure and lock" mechanism.…”
Section: Discussionmentioning
confidence: 84%
“…More recently, Qin et al have reported kinetic and freeenergy landscape analyses of a set of MD simulations, which suggested that the SL2 RNA associates with U1A by a process that involves an initial association followed by folding of the RNA into the bound conformation. 90 The three-step dissociation model proposed by Tang and Nilsson was supported by studies of association and dissociation by SPR and computational modeling studies. 41,44,81 The results of these investigations suggested that the U1A complex is formed by at least two steps that were termed the "lure and lock" mechanism.…”
Section: Discussionmentioning
confidence: 84%
“…6365 Most RNA binding proteins contain large numbers of basic amino acid residues, and electrostatic attraction to the RNA may drive the initial formation of non-specific and dynamic encounter complexes, as suggested for the RNA recognition motif (RRM) protein U1A. 66,67 …”
Section: Induced Fit In Rna-protein Recognitionmentioning
confidence: 99%
“…The mechanism of the binding reaction could entail trapping a single loop structure that can be bound by the protein (conformational capture) (Williamson 2000) or making one RNA:protein contact that facilitates subsequent rearrangements of RNA and protein to form the final complex (induced fit) (Frankel and Smith 1998); of course, the reality is likely to be more complicated. Indeed, several possible mechanisms and schemes for U1A binding to SLII have been proposed (Katsamba et al 2001;Pitici et al 2002;Hall 2002, 2004;Kormos et al 2007;Qin et al 2010;1 These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%